2015
DOI: 10.1136/openhrt-2015-000288
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation after heart valve surgery: cost analysis of healthcare use and sick leave

Abstract: BackgroundOwing to a lack of evidence, patients undergoing heart valve surgery have been offered exercise-based cardiac rehabilitation (CR) since 2009 based on recommendations for patients with ischaemic heart disease in Denmark. The aim of this study was to investigate the impact of CR on the costs of healthcare use and sick leave among heart valve surgery patients over 12 months post surgery.MethodsWe conducted a nationwide survey on the CR participation of all patients having undergone valve surgery between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…10 According to current guidelines, all patients received a physical examination and biochemical and echocardiographic assessment from the referral hospital following surgery. 11 Costs and outcomes were evaluated from the date of discharge and until 6 months post-surgery, which was considered an adequate length of follow-up, since costs are mainly incurred within the first months post-surgery, 8 and mortality rates are considered low following surgery. 4,5…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 According to current guidelines, all patients received a physical examination and biochemical and echocardiographic assessment from the referral hospital following surgery. 11 Costs and outcomes were evaluated from the date of discharge and until 6 months post-surgery, which was considered an adequate length of follow-up, since costs are mainly incurred within the first months post-surgery, 8 and mortality rates are considered low following surgery. 4,5…”
Section: Methodsmentioning
confidence: 99%
“…A recent Danish nationwide survey of patients undergoing heart valve surgery demonstrated no significant differences in total costs or other categories of primary care visits, inpatient hospital admissions, prescription medication or sick leave costs, and concluded that CR, when compared to non-participation, can be considered cost-neutral and may even offset more expensive outpatient visits. 8 However, the study contained no information on HRQL or other patient-reported outcomes, which are crucial to informing health policy planning regarding the attractiveness of CR as a routine practice. Within the field of CR, cost–utility analyses are particularly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have focused on different aspects of return to the workforce following open heart valve surgery: work status before surgery and participation in cardiac rehabilitation and the likelihood of returning to the workforce [1,12]. Thus, to our knowledge, this is the first study to investigate clinical characteristics and the association with return to the workforce.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, to prevent detachment from the workforce to the extent possible, a better understanding of the associated factors is warranted. Currently, research investigating interventions aiming at increasing the likelihood of returning to the workforce is sparse with current studies lacking statistical power or reporting conflicting results [12,24].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation